OTHR-24. Impact of physical activity on postural stability and coordination in children with posterior fossa tumor: randomized control phase III trial. (3rd June 2022) - Usama, Mahmoud; Abdelaziem, Faten H; Rashed, Wafaa M; Maher, Eslam; El Beltagy, Mohamed; Zekri, Wael
Abstract: BACKGROUND: Posterior fossa tumor is a type of brain tumor that is located at the borders of both the brain stem and cerebellum. The cerebellum is the brain region in charge of balance and coordination. Pediatric patients diagnosed with posterior fossa tumor have been reported to fall frequently. OBJECTIVES: The aim of this study is to investigate the effectiveness of balance and coordination training in these children. METHODS: This randomized control clinical trial was carried out between September 2020 and April 2021 at Children's Cancer Hospital-57357. The inclusion criteria of the participants were - patients with posterior fossa tumor in maintenance phase and, age between 5-12 years. The study participants were randomly assigned into three groups: Group I/Control group: they received Pilates core stability exercises program, Group II/Balance group: They received the same program plus HUMAC balance program, and Group III/Coordination group: They received the same program plus coordination exercises of BOT-2. Descriptive statistics for patients' characteristics were reported as medians and interquartile ranges for quantitative variables, frequencies, and percentages for qualitative ones. Significance level of P value was at <0.05. RESULTS: Sixty children including 38 boys and 22 girls were enrolled in this study. In all three groups, postural stability and coordination improved significantly in terms of modified clinical test of sensory integration of balance, center of pressure, limits of stability, bilateral coordination, and upper-limb coordination.CONCLUSION: The current study supports the value of adding postural stability and coordination training to the physiotherapy plan for children with posterior fossa tumor. Clinical trial information: RCT no#NCT04528316. Keywords: Posterior fossa tumor, Children, HUMAC, BOT-2, Postural stability, Balance, Coordination.